Design Thinking in Education: Developing a Cross-Subject Teacher Collaboration Platform for Creativity Assessment - Masriani, Elsa; Haeny, Nanda Abqari (The Future of Education Journal, 2025)
This study reports on the development of a digital platform designed to facilitate cross-subject collaboration among secondary school teachers in Indonesia for assessing students' creative works. Grounded in the Design Thinking methodology, the project progressed through the stages of Empathise, Define, Ideate, and Prototype. The platform addresses the gap in current assessment practices where creativity is undervalued due to limitations in teacher expertise and evaluation tools. By adopting a user-centred and co-design approach, involving teachers as active collaborators, the platform integrates principles of collaborative learning and computer-mediated communication. The article outlines the design process in detail, highlighting how Design Thinking guided the iterative development up to the prototyping phase, which produced a high-fidelity design ready for future testing.